H2 roaming chemistry and the formation of H3+ from organic molecules in strong laser fields. Issue 1 (December 2018) - Ekanayake, Nagitha; Severt, Travis; Nairat, Muath; Weingartz, Nicholas; Farris, Benjamin; Kaderiya, Balram; Feizollah, Peyman; Jochim, Bethany; Ziaee, Farzaneh; Borne, Kurtis; Raju P., Kanaka; Carnes, Kevin; et al.
Abstract Roaming mechanisms, involving the brief generation of a neutral atom or molecule that stays in the vicinity before reacting with the remaining atoms of the precursor, are providing valuable insights into previously unexplained chemical reactions. Here, the mechanistic details and femtosecond time-resolved dynamics of H3 + formation from a series of alcohols with varying primary carbon chain lengths are obtained through a combination of strong-field laser excitation studies and ab initio molecular dynamics calculations. For small alcohols, four distinct pathways involving hydrogen migration and H2 roaming prior to H3 + formation are uncovered. Despite the increased number of hydrogens and possible combinations leading to H3 + formation, the yield decreases as the carbon chain length increases. The fundamental mechanistic findings presented here explore the formation of H3 +, the most important ion in interstellar chemistry, through H2 roaming occurring in ionic species. H2 roaming is associated with H3 + formation when certain organic molecules are exposed to strong laser fields. Here, the mechanistic details and time-resolved dynamics of H3 + formation from a series of alcohols were obtained and found that the product yield decreases as the carbon chain length increases.